Development and Validation of Reversed-phase High-performance Liquid Chromatography Method for Simultaneous Estimation of Desonide and Curcumin in Topical Dosage Form (Asian Journal of Pharmaceutics (AJP), 2024)
A reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated tosimultaneously determine curcumin and desonide in both bulk and pharmaceutical dosage forms. This method ischaracterized by its simplicity, sensitivity, speed, specificity, precision, and accuracy. The mobile phase consistedof a mixture with a ratio of 65:35 v/v, and the flow rate was maintained at 0.8 mL/min. Chromatographic separationwas achieved using a C18 column (250 × 4.6 mm – 5 μm p.s), with ultraviolet detection performed at 240 nm.An injection volume of 20 μL was used. The retention times for desonide and curcumin were 3.45 and 7.51 min,respectively, resulting in distinct and well-defined chromatographic peaks. The respective percentage recoverieswere 99.56% and 99.87%. The suggested approach demonstrated strong linearity, accuracy, and precision, andit was effectively used to determine the medicines in pharmaceutical dosage forms. The current approach wascreated and successfully used to ascertain the quantities of curcumin and desonide in a combined formulation afterit was statistically validated in compliance with the ICH recommendations.